Using think pair share (tps) in teaching speaking - Zuhra (Institute of Computer Science (IOCS), 2023)
This study aims at finding whether Think Pair Share (TPS) in teaching speaking skills improves the students’ achievement. It was experimental research. This study was conducted at SMPN 8 Banda Aceh on the 8th level. There were 20 students. In collecting the data, the researcher distributed some tests and observation sheets. The test was about speaking test. The test which was distributed before treatment was called a pre-test and the test which was given after treatment was called a post-test. Pre-test and post-test need to be collected to evaluate the student’s achievement before and after the implementation of Think Pair Share (TPS). Then, the observation sheet aims to observe the students’ participation when the research was conducted. The finding revealed that the use of TPS improves students' speaking skills. The data were analyzed by using SPSS and Wilcoxon Signed Ranks Test Formula. Based on the output of “Test Statistics” revealed that Asymp.Sig. (2-tailed) was 0.000. The 0.000 is lower than 0.05 and it meant that the alternative hypothesis was accepted and the null hypothesis was rejected. In other words, Think Pair Share (TPS) improves the students’ speaking skills. The results show that the post-test score after treatment is higher than the pre-test score.